Work and family : towards new forms of reconciliation with social co-responsibility (ILO SantiagoCL, 2009)
Addresses the challenges posed by social inclusion and makes policy recommendations regarding how to advance toward more decent work, from a human rights perspective.
Bibliography: p. 143-146